2011
DOI: 10.1042/cbi20100083
|View full text |Cite
|
Sign up to set email alerts
|

Kojic acid, a secondary metabolite fromAspergillussp., acts as an inducer of macrophage activation

Abstract: KA (kojic acid) is a secondary metabolite isolated from Aspergillus fungi that has demonstrated skin whitening, antioxidant and antitumour properties among others. However, limited information is available regarding its effects on macrophages, the major cell involved in cell defence. The aim of the present study was to analyse whether KA affects functional properties related to macrophage activation, such as phagocytosis and spreading ability over a substrate. Treatment of resident macrophages with 50 μg/ml KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 48 publications
2
33
0
2
Order By: Relevance
“…Recently, we reported that KA could modulate macrophage activation through cytoskeleton rearrangement, increase cell surface exposure, and enhance the phagocytic process and superoxide anions (O 2 − ) production [18]. The antiamastigote effect observed in the present report showed that KA promotes a stimulatory effect in macrophages, killing the parasites.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Recently, we reported that KA could modulate macrophage activation through cytoskeleton rearrangement, increase cell surface exposure, and enhance the phagocytic process and superoxide anions (O 2 − ) production [18]. The antiamastigote effect observed in the present report showed that KA promotes a stimulatory effect in macrophages, killing the parasites.…”
Section: Discussionsupporting
confidence: 64%
“…The experiments were performed according to Rodrigues et al . (2011) [18] with some modification. After 24 h of growth, macrophages were incubated with 50 μg/mL of KA, 0.5 mg/mL of NBT and in the presence or absence of L.amazonensis promastigotes (ratio 10∶1) for one hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, kojic acid has been used as an antibiotic, pesticide, and analytical chemical (in the determination of thorium and rare earths) as recorded by many investigator [1012]. Utilization of industrial waste or by-products for the fungal production of useful products has been recommended by many investigations such as glycerol production by filamentous fungi using cheese whey [13–15], lipid, and sterol and ergosterol production by fungi using sugar cane molasses or cheese whey [16–18] and side-chain degradation and some biological transformation of progesterone by fungi using sugar cane molasses [19] and cyclosporin A production by fungi grown on agro-industrial wastes of some fruits, vegetables, and pickles as well as molasses and corn steeps [20–22]. The objective of this study was to study the following: the potentialities of kojic acid and production by 278 different fungal isolates; comparison between static and shaking cultivation methods for the production; optimization of both nutritional and environmental factors affecting the acid production; and utilization of 15 kinds of agro-industrial wastes or by-products by the high kojic acid producers for acid formation as well as production of this product on semi-industrial scale using a laboratory fermentor.…”
Section: Introductionmentioning
confidence: 99%
“…29,[45][46][47][48] In addition, it has also been shown that KA significantly enhances neutrophil phagocytosis and lymphocyte proliferation. 49,50 In this study, we have incorporated CS and PEG on the surface of MNPs as a first attempt to use them in antibacterial applications. Due to the importance of KA (and its derivatives) in antibacterial applications, as shown from the previous pharmacological studies, KA was chosen as the model active substance in this study.…”
mentioning
confidence: 99%